Learning Achievement Handball Basic Skills by Student Teams Achievement Divisions (STAD) of Mathayomsuka 3 Students at Strisuksa School - Kongpolprom , Rattanaporn; Sawassdee, Sushila; Pratoomon, Ruangwat; Suwannachairob, Wanpen; Orasri , Naree (Interdisciplinary Academic and Research Journal, 2023)
The Basic Education Core Curriculum for the year 2008 (B.E. 2551) in Thailand has outlined the content of the subject "Physical Education." It states that students should learn about various forms of movement, participate in physical activities and sports, both individual and team-based, from both Thai and international perspectives. They should also learn to adhere to rules, regulations, and agreements when participating in physical activities and sports, as well as develop sportsmanship. The objectives of this research are as follows: 1) To determine the effectiveness of the Student Teams Achievement Divisions (STAD) cooperative learning method in improving the basic skills of handball. This will be assessed using the 90/90 criteria. 2) To compare the learning outcomes of basic handball skills before and after using the STAD cooperative learning method. 3) To examine the satisfaction level of students towards the use of the STAD cooperative learning method for teaching basic handball skills. The research tools used in this study include the STAD cooperative learning method, a test measuring learning outcomes of basic handball skills, a satisfaction questionnaire regarding the STAD cooperative learning method, and statistical analysis tools such as mean, standard deviation, and t-test. The research findings revealed that: 1) The effectiveness of the STAD cooperative learning method in improving basic handball skills had a score of 87.95/92.56. 2) The learning outcomes after using the STAD cooperative learning method were significantly higher than before, with statistical significance at the .05 level. 3) satisfaction with learning management about basic handball skills by using the cooperative learning management plan (STAD), overall satisfaction was at a high level.